2011
DOI: 10.1016/j.colsurfb.2011.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of anti-fouling PEGylated surfaces probed by fluorescence correlation spectroscopy

Abstract: The present work reports on in situ observations of the interaction of organic dye probe molecules and dye-labeled protein with different poly(ethylene glycol) (PEG) architectures (linear, dendron, and bottle brush). Fluorescence correlation spectroscopy (FCS) and single molecule event analysis were used to examine the nature and extent of probe–PEG interactions. The data support a sieve-like model in which size-exclusion principles determine the extent of probe–PEG interactions. Small probes are trapped by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…First, agarose is known to form relatively large pores that can range from 9 to 90 nm in size [Langford et al ., ; Yao et al ., ]. As we have recently shown, soft porous substrates can form sieve‐like structures that sterically hinder the diffusion of probes such as dyes and proteins via hydrostatic effects [Daniels et al ., ]. Other proposed steric interactions that have been identified by FCS include coupling to higher‐order polymer vibrational modes [Wang and Zhu ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, agarose is known to form relatively large pores that can range from 9 to 90 nm in size [Langford et al ., ; Yao et al ., ]. As we have recently shown, soft porous substrates can form sieve‐like structures that sterically hinder the diffusion of probes such as dyes and proteins via hydrostatic effects [Daniels et al ., ]. Other proposed steric interactions that have been identified by FCS include coupling to higher‐order polymer vibrational modes [Wang and Zhu ].…”
Section: Resultsmentioning
confidence: 99%
“…Single‐molecule imaging and the extensive successful practical use of agarose‐based adsorbents offer strong evidence that there are only negligible nonspecific chemical interactions between the protein and the agarose. Thus, on the basis of both our experimental analysis and our more detailed recent study of sieve‐like behavior of porous soft interfaces [Daniels et al ., ], we believe that the primary contributor to the modification of protein mobility at the water/agarose interface is steric interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in order for the contact of the protein's hydrophobic residues with the like surface to be maximized, and may be revealed by the native shape of the molecule ''squashing'' upon adsorption to hydrophobic surfaces. A better understanding of the effects of adsorption on protein conformation may also have important implications in the field of immunology, where the use of antibody-antigen assays involving the adsorption of protein antigen onto a solid surface are seeing widespread use [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that at the basic pH, when the brush is in its collapsed state, the brush did not garner interaction of the probes. We recently explored the construction of molecular sieves using polymer brushes, and reported that pore size can greatly influence the inclusion and exclusion of probes from the brush, 19 resulting in a molecular sieve. 35 The high pH data shown in Figure 6 is consistent with the earlier studies and suggests that the more dense collapsed brush excludes the probes.…”
Section: Resultsmentioning
confidence: 99%